Euler consumption equation with non-separable preferences over consumption and leisure and collateral constraints - Juha Kilponen (Bank of Finland, 2009)
This paper derives and estimates an aggregate Euler consumption equation which allows one to compare the importance of collateral constraints and non-separability of consumption and leisure as alternative sources of excess sensitivity of consumption to current income. Estimation results suggest that during a severe financial distress both non-separability and collateral constraints are needed to capture excess sensitivity of consumption to current economic conditions. During more tranquil times, evidence on collateral effects is more limited and non-separability is sufficient to make the Euler consumption equation agree well with the data.
URN:NBN:fi:bof-20140807273
Keywords: E21; E32; E44; 330; housing; financial distress; excess sensitivity of consumption